2022
DOI: 10.1021/acssuschemeng.1c07762
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Boron on the Interface Modulation of the Pd/TiO2 Catalyst for Direct Synthesis of H2O2

Abstract: Rational modulation of metal−support interaction is an effective strategy to enhance the catalytic performance of a supported catalyst. Here, both the activity and selectivity for the direct H 2 O 2 synthesis from H 2 and O 2 are enhanced by the doping of boron atoms at the interface of Pd and TiO 2 . With boron doping, the selectivity and productivity of H 2 O 2 are remarkedly increased from 63.4% and 2.99 mol H 2 O 2 g Pd −1 h −1 to 80.1% and 3.65 mol H 2 O 2 g Pd −1 h −1 in a triphase semicontinuous reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…This was also confirmed by XRD, where the intensity of the diffraction peak (111) of Au 3 Cu decreased with the increase of reduction time. According to previous studies, it was found that the performance of the catalyst is also affected by the chemical state of Pd. , In bimetallic catalysts, the electronic effect is also not neglected. However, from the results of XPS (Figure a and Table ), the chemical state of Pd in all Au 3 Cu@AuPd catalysts shows no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…This was also confirmed by XRD, where the intensity of the diffraction peak (111) of Au 3 Cu decreased with the increase of reduction time. According to previous studies, it was found that the performance of the catalyst is also affected by the chemical state of Pd. , In bimetallic catalysts, the electronic effect is also not neglected. However, from the results of XPS (Figure a and Table ), the chemical state of Pd in all Au 3 Cu@AuPd catalysts shows no significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…The Pd3d spectrum, as shown in Figure 3d, adduces two peaks: one at 341.1 eV corresponding to Pd3d3/2, and the other at 335.8 eV for Pd3d5/2. The appearance of Pd 2+ peak may be due to the partial oxidation of the Pd surface since the Pd particles are very minute in the Pd-TiO2 film sensor [34]. The Ti2p 3/2 peak has a binding energy of 463.9 eV, whereas the low-intensity Ti2p 1/2 peak has a binding energy of 458.1 eV, thus indicating the presence of a Ti 4+ oxidation state [32].…”
Section: Elemental Analysismentioning
confidence: 99%
“…The Pd3d spectrum, as shown in Figure 3d, adduces two peaks: one at 341.1 eV corresponding to Pd3d 3/2 , and the other at 335.8 eV for Pd3d 5/2 . The appearance of Pd 2+ peak may be due to the partial oxidation of the Pd surface since the Pd particles are very minute in the Pd-TiO 2 film sensor [34].…”
Section: Elemental Analysismentioning
confidence: 99%
“…H 2 O 2 is widely recognized as one of the most efficient and environmentally friendly oxidants. It exhibits excellent oxidation properties across all pH ranges, which makes it highly versatile in various applications, such as chemical synthesis, papermaking, mining, environmental remediation, and disinfection . With the growing emphasis on green production, the demand for H 2 O 2 is expected to increase significantly .…”
Section: Introductionmentioning
confidence: 99%